Pengembangan Aplikasi Biodata Mahasiswa Berbasis Desktop dengan Microsoft Visual Basic 6.0 sebagai Solusi Pengelolaan Data Efisien - Ardiansyah, Muhammad Ridho; Davizan, Serry; Anggraini, Amelia; Pramudhito, Anggoro Aryo; Sari, Indah Rahma; Paramita, Bella (Journal of Social and Community Service, 2024)
Efficient student data management is one of the important needs in educational institutions. However, in many cases, data management is still done manually or using less structured methods, which has the potential to cause errors and hinder the administration process. To overcome these problems, this community service program aims to develop and implement a desktop-based student biodata application using Microsoft Visual Basic 6.0. This application is designed to facilitate student data management, including input, search, update, and storage of data in a structured manner. Application development is carried out through the stages of needs analysis, system design, coding, and testing. The Microsoft Access database is used as a data storage medium, integrating Visual Basic 6.0 capabilities in efficient and user-friendly data management. The results of this activity show that the application developed has succeeded in increasing the efficiency of student data management. Users can easily enter, search, and modify data without the need for in-depth technical knowledge. In addition, application usage training provided to target users helps ensure the sustainability of application implementation in related institutions. With this application, it is hoped that student data management will be more organized, faster, and more accurate, thus providing a positive impact on administrative efficiency and decision-making in educational institutions.